2022
DOI: 10.3389/fphar.2022.927984
|View full text |Cite|
|
Sign up to set email alerts
|

Three Naturally-Occurring Psychedelics and Their Significance in the Treatment of Mental Health Disorders

Abstract: Classical psychedelics represent a family of psychoactive substances with structural similarities to serotonin and affinity for serotonin receptors. A growing number of studies have found that psychedelics can be effective in treating various psychiatric conditions, including post-traumatic stress disorder, major depressive disorder, anxiety, and substance use disorders. Mental health disorders are extremely prevalent in the general population constituting a major problem for the public health. There are a wid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 246 publications
0
2
0
Order By: Relevance
“…Psychedelic therapy is increasingly being recognized as a transformative approach to mental health care [17]. A growing body of research suggests that psychedelic substances, such as psilocybin, have significant therapeutic potential for a range of mental health disorders, including depression, anxiety, post-traumatic stress disorder (PTSD), eating disorders, and various forms of addiction [17][18][19].…”
Section: Employing Psychedelic Therapy In the Treatment Of Psychologi...mentioning
confidence: 99%
“…Psychedelic therapy is increasingly being recognized as a transformative approach to mental health care [17]. A growing body of research suggests that psychedelic substances, such as psilocybin, have significant therapeutic potential for a range of mental health disorders, including depression, anxiety, post-traumatic stress disorder (PTSD), eating disorders, and various forms of addiction [17][18][19].…”
Section: Employing Psychedelic Therapy In the Treatment Of Psychologi...mentioning
confidence: 99%
“…The table below shows results from human hepatocytes assays conducted with D 6 -DMT and D 8 -DMT, which indicated that intrinsic clearance of D 8 -DMT displayed a 2.1 change from that of DMT (SPL026). …”
Section: Important Compound Classesmentioning
confidence: 99%